2020
DOI: 10.1186/s12884-020-03153-x
|View full text |Cite
|
Sign up to set email alerts
|

Healthy eating and physical activity among breastfeeding women: the role of misinformation

Abstract: Background Eating healthy, being physically active and breastfeeding can greatly support a new mother’s physiological and psychological health. However, within the United States, only 8.5% of women are meeting fruit and vegetable recommendations and only 35% of women are maintaining their pre-pregnancy physical activity after childbirth. Preliminary investigations suggest barriers such as lack of time and knowledge hinder a breastfeeding woman’s ability to eat well and be physically active. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…34 Unfortunately, social media has also been associated with presenting inaccurate education. 35 Thus to combat isolation innovative strategies to provide support via mHealth technologies such as mobile health applications should continue to be improved to ensure mothers are not only receiving support but accurate support. 36 Second, supportive normalization of breastfeeding was identi ed at the community and organizational levels but a lack of normalization was reported at the individual and interpersonal levels.…”
Section: Discussionmentioning
confidence: 99%
“…34 Unfortunately, social media has also been associated with presenting inaccurate education. 35 Thus to combat isolation innovative strategies to provide support via mHealth technologies such as mobile health applications should continue to be improved to ensure mothers are not only receiving support but accurate support. 36 Second, supportive normalization of breastfeeding was identi ed at the community and organizational levels but a lack of normalization was reported at the individual and interpersonal levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that eating healthy, being physically active, and breastfeeding can be of great help to a new mother's physiological and psychological health. However, the adherence to fruit and vegetable intake recommendations and physical activity adapted to their stage of the life cycle is low [34]. Women need greater access to education and resources related to healthy eating and physical activity during breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…Women need greater access to education and resources related to healthy eating and physical activity during breastfeeding. This information should come from healthcare professionals and not from the internet [34,35]. Furthermore, it has been demonstrated that a Mediterranean diet protects against depression and mood disorders, also reducing their intensity [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The rst step in the analysis process was a direct content analysis which included two researchers reviewing all interview transcripts in their entirety twice. 32 The two researchers separately identi ed and coded statements that directly related to one of the SEM levels. Both researchers kept memo notes throughout their coding process and came together to discuss discrepancies.…”
Section: Introductionmentioning
confidence: 99%